1992
DOI: 10.1152/ajpgi.1992.262.5.g883
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of palmitate by hepatocyte suspensions: facilitation by albumin?

Abstract: Albumin-dependent uptake of unbound [3H]palmitic acid by hepatocytes isolated from female rat livers was studied and the experimental results compared with the predictions of a noncompartmental diffusion-reaction theory for the cellular uptake of protein-bound ligands. The outright theoretical predictions involve values for the parameters of the system, some newly measured (hepatocyte radii and the rate constant for the dissociation of palmitate-albumin complex) and some taken from the literature (diffusion co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…Pond et al (1992) reported that facilitation mechanism was involved in uptake of palmitate by hepatocyte suspensions. They found that the measured unbound clearance of [ 3 H]palmitic acid, defined as the initial uptake velocity divided by the unbound [ 3 H]palmitic acid concentration in the medium, was enhanced 6.6-fold as the concentration of human serum albumin was increased from ϳ5 to 480 M. In fact, in many cases, the uptake rate appears to be determined more by the bound than by the unbound ligand concentration (Weisiger et…”
Section: Discussionmentioning
confidence: 99%
“…Pond et al (1992) reported that facilitation mechanism was involved in uptake of palmitate by hepatocyte suspensions. They found that the measured unbound clearance of [ 3 H]palmitic acid, defined as the initial uptake velocity divided by the unbound [ 3 H]palmitic acid concentration in the medium, was enhanced 6.6-fold as the concentration of human serum albumin was increased from ϳ5 to 480 M. In fact, in many cases, the uptake rate appears to be determined more by the bound than by the unbound ligand concentration (Weisiger et…”
Section: Discussionmentioning
confidence: 99%
“…1B). In this work, permeability has not been adjusted for fraction unbound in perfusate as described previously (12), because there have been suggestions that perfusate albumin facilitates palmitate uptake (2,24).…”
Section: Ajp-gastrointest Liver Physiolmentioning
confidence: 99%
“…It was argued that in the intact organ, albumin facilitation would be predicted to be present when the dissociation of the protein-ligand complex is slow and rate limiting for the observed uptake. The hypothesis was questioned by Bass and Pond who introduced an alternative hypothesis, the idea that phenomena occurring in a stagnant layer surrounding the cells can explain albumin facilitation (Bass and Pond 1988;Pond et al 1992). Albumin simply helps the organic anion to diffuse across this layer, which means that the albumin effect is caused by events inside this stagnant layer and should be independent of the nature of the membrane.…”
Section: Physiology Of the Uptake Of Long-chain Fatty Acids Plasma Almentioning
confidence: 99%
“…However, although the studies with artificial membranes helped to abandon the albumin-receptor hypothesis, they could not provide insight into the manner in which hepatocytes take up fatty acids (Schwab and Goresky 1991). Pond et al (1992) measured [3H]palmitate uptake in isolated rat hepatocytes in the presence of 5-80 gM human serum albumin (HSA) and calculated the clearance of the fatty acid at each albumin concentration. Clearance was determined by dividing the measured uptake rate by the total fatty acid concentration in the extracellular fluid.…”
Section: Physiology Of the Uptake Of Long-chain Fatty Acids Plasma Almentioning
confidence: 99%